Intermetallic germanides with non-centrosymmetric structures derived from the Yb3Rh4Sn13 type. Issue 12 (23rd February 2015) - Gumeniuk, R.; Schöneich, M.; Kvashnina, K. O.; Akselrud, L.; Tsirlin, A. A.; Nicklas, M.; Schnelle, W.; Janson, O.; Zheng, Q.; Curfs, C.; Burkhardt, U.; Schwarz, U.; et al.
Abstract : New germanides with composition RE3 Pt4 Ge13 (RE = Y, Pr, Sm, Gd, Tb, Tm) have been prepared by high-pressure, high-temperature synthesis. Abstract : New germanides with composition RE3 Pt4 Ge13 (RE = Y, Pr, Sm, Gd, Tb, Tm) have been prepared by high-pressure, high-temperature synthesis. Their crystal structures have been refined, and the relationship of this new rhombohedral and monoclinic structure types with the primitive cubic Yb3 Rh4 Sn13 prototype is discussed. Band structure calculations within density functional theory confirm the distorted rhombohedral and monoclinic structural arrangements to be energetically more favorable than the simple cubic one. X-ray absorption spectroscopy and magnetic susceptibility measurements indicate that the RE-atoms are in the +3 oxidation state in all studied compounds.